Kajian Profil Lulusan STAIN Samarinda Program Studi Pendidikan Agama Islam (PAI) Tahun 2009 – 2013 dengan Pendekatan Tracer Study - Wahdatunnisa, Wahdatunnisa (LP2M IAIN Samarinda, 2014)
Islamic higher education is targeted to create a high qualified human resources. A tracer study could be used to gain a data about the flaws, both of the process of education and the process of learning, of the quality of Islamic higher educations. by knowing the flaws, it can be used to make a better planning in the future. The problem of this study are: 1) How is the appropriateness of the work-field of the alumnae and the study program of Islamic education program of IAIN Samarinda?, 2) How is the contributions of the curriculum of Islamic education program of IAIN Samarinda to the work-field?, 3) How is the improvement of curriculum of Islamic education program of IAIN Samarinda to create a high qualified alumnae? This is and evaluative research design which is objected to describe the profil of alumnae and the curriculum relevance at Islamic education program at IAIN Samarinda. In this study, the researcher used interview and documentation to collect the data. The researcher used interview guide and recording tools as the instruments. The result of the study shows that: firstly, most of alumnae work in the schools as teachers or administration staff. Secondly, curriculum of PAI at STAIN Samarinda proves in supporting the work of alumnae. Thirdly, the improvement of curriculum can be done by adjusting the content of curriculum with the work field, improving lecturers’ qualification, erlarging the practicum, empowering the alumnae with some competencies, and strengthening the subjects of teachers and educational content.